Comparative Study of Flank Cams Manufactured by WEDM and Milling Processes - Irene Buj-Corral; Enrique Zayas-Figueras; Àngels Montaña-Faiget (Metals, 2020)
Cam-follower mechanisms are usually employed in different machines, like combustion engines, sewing machines, machine tools, etc. In the present paper, the option to manufacture cams utilizing wire electrical discharge machining (WEDM) has been considered. For this, surface roughness and shape error of cam profiles manufactured by the processes of milling and wire electrical discharge machining (WEDM) are presented. The methodology used covers different stages: design, prototyping, manufacturing, and measurement of the cams. As a reference, a cam-follower mechanism from a motorcycle internal combustion engine has been used. A reverse engineering process has been performed to determine the geometrical parameters of the mechanism, which are used for the synthesis of the profile of the cam and its subsequent design. The manufacturing process of the cams has been assisted by CAD-CAM (Computer Assisted Drawing-Computer Assisted Manufacturing) software. Using fused filament fabrication (FFF), a physical prototype of the cam has been manufactured, in order to validate the goodness of the design. Finally, the roughness and shape parameters have been measured on the contour surface of the cams. The arithmetical mean roughness Ra value of the milled cam was 0.269 μm, below the requirement of 0.4 μm, and shape error was 18 μm, below 50 μm. Shape error of the WEDM cam of 48 μm meets the requirements for cams. However, the Ra value of 1.212 μm, exceeded the limit. For this reason, a finish operation is recommended in this case. Some advantages of WEDM cams over milled cams are that different conductive materials can be employed, more complex shapes can be obtained, and that, in rough operations, the amount of material to be removed in subsequent operations is considerably reduced.